Perspectives de valorisation de l'eau d'irrigation dans les pays du Maghreb - Ben Mechlia N. (Water management for drought mitigation in the Mediterranean, 2004)
Irrigation has been practiced in North Africa since the romain era. When new fruit species and substantial know how were brought into the region by Arabs irrigation has known a flourishing period. Large irrigation schemes have known a tremendous development during the second half of the twentieth century. Rapidly, they completed the mobilization of their renewable resources and stretched their use of irrigation water to a maximum limit. Presently, the region is facing severe water shortages and the irrigated sector is enduring the effects of Globalization. Consequently, innovative ideas are required so access to irrigation could remain a direct way to wealth. One solution relates to the valorization of the region climatic resources that allow crops of special types and qualities to be unique. Dates and other fruits have comparative advantage that could benefit the sector. Vegetables produced early in the season and biological product could conquer important foreign markets.
Special Session on 'Water Management for Drought Mitigation in the Mediterranean' at the Regional Conference on Arab Water 2004, 2004/04/12-16, Cairo (Egypt)